Emerging ethical aspects of drug addiction: Harm Reduction - De Filippis, Vincenzo; Miranda, Gonzalo (Medicina e Morale, 1995)
The article aims, from a technical-scientific and ethical point of view, to examine the strategy tried out for the first time in Great Britain, called "Harm Reduction" (HR). HR is a social policy which aims to decrease the negative effects of drug consumption by encouraging contact with the largest possible number of drug addicts in order to put more of them on the road to responsibility and solidarity. The basis of HR is: 1. the awareness that the problems is not drug but the way it is used; 2. a programme that concentrates on the person rather than on the drug; 3. the awareness that no therapeutic mode! is val id for everyone. The positive aspects of HR are the points mentioned above, wheras the negative aspects, in the light of the experience gained in Great Britain, are as follows: 1. the lack of a concrete attempt to help the person completely rccuperate, so the instruments adopted risk reiterating the chronic nature of drug addiction; 2. the interventions are rendered "ideological"; 3. the prevalence of the interests of the population over those of the person in the application of the overall health budget; 4. the insufficient number of operators. In conclusion, HR as a simple "tesser evil" can not be accepted ethically in that it encourages a further lack of responsibility and the increasingly chronic aspect of drug addiction. HR can only be considered valid as the initial phase of a project that aims to overcome drug addiction, through strategies like a closer communication between the health worker and the patient, sending the drug addict to therapeutic communities and reintegration at work and in the family.